The odds of progressing from first to second birth in the context of HIV/AIDS and fertility decline in Agincourt rural area of South Africa. - Shabangu, Goodness Mildred (My University, 2011)
Introduction: Many regions in the Sub-Saharan Africa have undergone fertility decline and some countries are still continuing to drop even below replacement level. South Africa is one of these countries. However, there are still high levels of teenage and non-marital fertility. Fertility in South Africa is characterized with early first births and delayed subsequent births among teenagers than . women who do not have a birth as teenagers This raises a concern that timing of first birth and subsequent spacing of births is becoming a major determinant of fertility decline that is not yet receiving substantial research attention. This study examines the age and period effects of progression from first to second birth and helps to fill this gap in the research on fertility in South Africa., Methodology: Using a sample of 12,942 women. derived from the 1993 and 2007 Agincourt Health and Demographic Surveillance Site (AHDSS) data the study examine the age and period effect on birth spacing and intervals in an era of stalling fertility by modeling birth intervals from first live births to second births. With the assumption that teenage fertility is higher at first birth and that second birth intervals are longer for teenage mothers as compared to older mothers. For data analysis Chi squared tests were run to determine the distribution of births between teenage mothers and other first time mothers across the defined characteristics. I use logistic regression to assess the association between age/period effects on the likelihood of having a second birth within five years. Results were interpreted at 95% CI. Results: Only 40% of the sample had a second birth within 5 years of both periods. While there is an overall decline in fertility in second period compared to the first, teenage fertility has increased from 34% to 40% of first births. However, older moms have higher likelihood of second births than teen moms with the odds of young moms dropping and becoming closer to those of teen moms over time. Age, marital status at first birth, education, refugee status, and child mortality have a significant effect on the odds of progressing to a second birth in the second period. Conclusions and recommendations: Increasing progression likelihoods among married women combined with child mortality may be evocative of HIV/AIDS effects on progression, necessitating further research to understand the effects of progression on fertility decline, taking into consideration use of contraceptives, socio-economic and education policies affecting sexual and reproductive health and the effects of HIV/AIDS.